2019
DOI: 10.3390/antiox8040097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antioxidant Enzymes in Patients with Uterine Polyp, Myoma, Hyperplasia, and Adenocarcinoma

Abstract: We previously found that compared to patients with benign uterine diseases (polyps, myomas), patients with premalignant (hyperplasia simplex and complex) and malignant (adenocarcinoma) lesions had enhanced lipid peroxidation and altered uterine antioxidant enzyme (AOE) activities. To further elucidate the mechanism of the observed changes, we examined protein and mRNA levels of copper-zinc superoxide dismutase (CuZnSOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
4
1
Order By: Relevance
“…Increased GSH levels may thus reflect the allowance of survival of cells with altered metabolism [38] and reflect GSH-associated cytoprotection. Nevertheless, since the free glutathione in the serum is not directly reflecting the redox state inside the endometrial cells, its levels and the activity of the related enzymes (GPx, GR, and GST) in the tissue do not correlate with the results reported herein [39].…”
Section: Discussioncontrasting
confidence: 62%
“…Increased GSH levels may thus reflect the allowance of survival of cells with altered metabolism [38] and reflect GSH-associated cytoprotection. Nevertheless, since the free glutathione in the serum is not directly reflecting the redox state inside the endometrial cells, its levels and the activity of the related enzymes (GPx, GR, and GST) in the tissue do not correlate with the results reported herein [39].…”
Section: Discussioncontrasting
confidence: 62%
“…Considering that most types of tumor cells have low intrinsic levels of antioxidant enzymes compared with non‐tumor cells, tumor cells may not be able to efficiently detoxify higher concentrations of H 2 O 2 (Marklund, Westman, Lundgren, & Roos, 1982; Oberley & Oberley, 1997). A study evaluated the expression of antioxidant enzymes in gynecological disorders and identified that endometrial adenocarcinoma cells have low levels of catalase (CAT) enzyme, responsible for the decomposition of H 2 O 2 in water and oxygen (Todorović et al, 2019). Cancer cells that have a limited amount of CAT are sensitive to a high level of H 2 O 2 and end up being attacked by the generated hydroxyl radicals and induced to cell death (Birben, Sahiner, Sackesen, Erzurum, & Kalayci, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the advancement of uterine lesion formation depends on both the type of enzymes involved and the course of endometrial transformation. These observations will contribute to the understanding of the molecular mechanisms underlying oxidative stress mediated disorders (17) .…”
Section: Fig 5 Intramural Myoma -Uterine Tumor With Mixed Echogenicit...mentioning
confidence: 87%